Linking mechanisms of periodontitis to Alzheimer's disease. Issue 2 (April 2020) - Sadrameli, Mahtab; Bathini, Praveen; Alberi, Lavinia
Abstract : Purpose of review: The review article discusses the association between periodontal disease and the development of dementia. Recent findings: In the last decade, increasing evidence has pointed to a microbial and inflammatory origin for Alzheimer's disease with the discovery of oral and airway bacteria, viruses, and fungal species in the brain of patients with Alzheimer's disease. Furthermore, recognized as the culprit of neural network dysfunction, β-amyloid oligomeric species have antimicrobial properties reinforcing the idea that dysbiosis in the host–microbiota interaction can be at the origin of dementia. Periodontitis (gum disease), a persistent low-grade inflammatory condition, caused by pathogenic microorganisms, has been linked to an increased β-amyloid burden and cognitive disabilities later in life. Summary: The pathogens of periodontal disease and the subsequent chronic inflammatory responses have significant implications on the development of Alzheimer's disease. The exact molecular mechanism by which Porphyromonas gingivalis and periodontal disease are involved in the pathogenicity of Alzheimer's disease is not currently evident. Understanding this causality can be instrumental in the development of treatments for this yet uncurable disease.